2001
DOI: 10.1046/j.1525-1497.2001.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Counseling on Colorectal Cancer in Rural Primary Care Practices*

Abstract: To better understand colorectal cancer (CRC) screening practices in primary care, medical students directly observed physician-patient encounters in 38 physician offices. CRC was discussed with 14% of patients 50 years of age; 87% of discussions were initiated by the physician. The rate of discussions varied among the practices from 0% to 41% of office visits. Discussions were more common for new patient visits, with younger patients, and in the 24% of offices that utilized flow sheets. The frequency of CRC di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Although the act of completing a survey may have subsequently prompted physicians to discuss weight loss with other patients, in several prior studies of physician behavior in our practice-based network, we observed no appreciable change in counseling over a 6-week-period on topics such as smoking, cancer screening, and exercise, suggesting that research activities within a busy medical practice influence physician behavior very little over the course of a brief study. 37,38 This study extends the research on perceptions about weight in primary care by including nonmetropolitan practices and by surveying both patients and physicians in order to assess directly for patient-physician discrepancies. Future work is needed to expand the findings to a larger and more diverse population and to describe and verify counseling behavior through direct observation.…”
Section: Discussionmentioning
confidence: 92%
“…Although the act of completing a survey may have subsequently prompted physicians to discuss weight loss with other patients, in several prior studies of physician behavior in our practice-based network, we observed no appreciable change in counseling over a 6-week-period on topics such as smoking, cancer screening, and exercise, suggesting that research activities within a busy medical practice influence physician behavior very little over the course of a brief study. 37,38 This study extends the research on perceptions about weight in primary care by including nonmetropolitan practices and by surveying both patients and physicians in order to assess directly for patient-physician discrepancies. Future work is needed to expand the findings to a larger and more diverse population and to describe and verify counseling behavior through direct observation.…”
Section: Discussionmentioning
confidence: 92%
“…Patient survey items (44) [23][24][25][26] ; to ensure respondent anonymity, we did not record race or ethnicity.…”
Section: Survey Measuresmentioning
confidence: 99%
“…10,12,15 However, physicians do not consistently recommend CRCS to each eligible patient. 10,[16][17][18] Although multiple studies have investigated barriers and facilitators of CRCS, the majority have focused on the patient perspective. 19,20 Fewer have focused on the physician's perspective.…”
mentioning
confidence: 99%